Laboratory diagnosis of chronic myelomonocytic leukemia and progression to acute leukemia in association with chronic lymphocytic leukemia: morphological features and immunophenotypic profile - Santos,Iris Mattos (2012)
Chronic myelomonocytic leukemia is a clonal stem cell disorder that is characterized mainly by absolute peripheral monocytosis. This disease can present myeloproliferative and myelodysplastic characteristics. According to the classification established by the World Health Organization, chronic myelomonocytic leukemia is inserted in a group of myeloproliferative/myelodysplastic disorders; its diagnosis requires the presence of persistent monocytosis and dysplasia involving one or more myeloid cell lineages. Furthermore, there should be an absence of the Philadelphia chromosome and the BCR/ABL fusion gene and less than 20% blasts in the blood or bone marrow. Phenotypically, the cells in chronic myelomonocytic leukemia can present myelomonocytic antigens, such as CD33 and CD13, overexpressions of CD56 and CD2 and variable expressions of HLA-DR, CD36, CD14, CD15, CD68 and CD64. The increase in the CD34 expression may be associated with a transformation into acute leukemia. Cytogenetic alterations are frequent in chronic myelomonocytic leukemia, and molecular mutations such as NRAS have been identified. The present article reports on a case of chronic myelomonocytic leukemia, diagnosed by morphologic and phenotypical findings that, despite having been suggestive of acute monocytic leukemia, were differentiated through a detailed analysis of cell morphology. Furthermore, typical cells of chronic lymphocytic leukemia were found, making this a rare finding.